Positive pole piece, preparation method thereof and lithium ion battery
By using different types of binders in the active coating of the positive electrode sheet of the lithium-ion battery, changing the tortuity and porosity, the problem of deterioration in the magnification and cycling performance of high-plane density batteries is solved, and the goal of improving battery performance and energy density without increasing the proportion of conductive agents is achieved.
Patent Information
- Application Number
- CN202411808938.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-01-18
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art will deteriorate when increasing the electrode surface density of lithium-ion batteries, and when improving electrode conductivity by increasing the proportion of conductive agents, the energy density of the battery will be reduced.
By introducing different types of binders into the first active coating and the second active coating, the tortuosity and porosity of the positive electrode sheet are changed, so that the tortuosity of the second active coating is smaller than that of the first active coating and the porosity is larger than that of the first active coating, thereby increasing the diffusion rate of lithium ions and reducing the concentration polarization of the surface layer of the electrode sheet.
It significantly improves the battery's magnification and cycling performance without increasing the proportion of conductive agent, effectively reducing the resistivity of the pole sheet and improving the energy density of the battery.
Smart Images

Figure BDA0005180037040000151 
Figure BDA0005180037040000161 
Figure BDA0005180037040000162
Abstract
Description
[0001] This application claims the priority of patent application No. 202410076099.7 (the filing date of the prior application is 2024-01-18, and the name of the invention is: A positive electrode plate, a preparation method thereof, and a lithium-ion battery). Technical Field
[0002] The present invention belongs to the technical field of battery materials, and in particular relates to a positive electrode plate and a preparation method thereof, and a lithium ion battery. Background Art
[0003] As the requirements for the driving range of lithium-ion battery electric vehicles increase, the energy density of lithium-ion batteries will inevitably be increased accordingly. From the perspective of battery design, increasing the surface density of the electrode is an effective way to increase the energy density of the battery. However, as the surface density of the electrode increases, the rate and cycle performance of the battery will deteriorate. The existing technology usually improves the conductivity of the electrode by increasing the proportion of the positive electrode conductive agent to meet the requirements of rate and cycle performance.
[0004] However, although increasing the proportion of conductive agent can improve the rate performance of the battery to a certain extent, as the proportion of conductive agent increases, the proportion of the main material will decrease accordingly, which in turn will reduce the energy density of the battery.
[0005] Therefore, how to improve the rate and cycle performance of high surface density batteries without increasing the proportion of conductive agent is a major technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a positive electrode plate and a method for preparing the same, and a lithium-ion battery. The present invention introduces different types of binders into the first active coating and the second active coating, thereby changing the tortuosity and porosity of the positive electrode plate, so that the tortuosity of the second active coating is smaller than that of the first active coating, and the porosity of the second active coating is larger than that of the first active coating, which effectively improves the diffusion rate of lithium ions during the charge and discharge process, reduces the concentration polarization of the surface of the plate, and significantly improves the rate and cycle performance of the battery. In particular, the positive electrode plate can achieve the goal of improving the rate and cycle performance without increasing the proportion of the conductive agent, and can effectively reduce the resistivity of the plate and improve the energy density of the battery.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a positive electrode sheet, the positive electrode sheet comprising:
[0009] Positive electrode current collector;
[0010] A first active coating disposed on at least one side of the positive electrode current collector, wherein the raw materials of the first active coating include a first main material, a first conductive agent and a low swelling binder;
[0011] A second active coating is disposed on a surface of the first active coating on a side relatively away from the positive electrode current collector, wherein raw materials of the second active coating include a second main material, a second conductive agent and a high swelling binder.
[0012] The present invention introduces different types of binders into the first active coating and the second active coating, thereby changing the tortuosity and porosity of the positive electrode plate, so that the tortuosity of the second active coating is smaller than that of the first active coating, and the porosity of the second active coating is larger than that of the first active coating, so that the lithium ions in the first active coating are released and migrate to the second active coating, and the lithium ions in the second active coating are also released at the same time, which effectively improves the diffusion rate of lithium ions during the charge and discharge process, reduces the concentration polarization of the surface of the plate, and significantly improves the rate and cycle performance of the battery.
[0013] It is particularly important to note that the positive electrode plate can achieve the goal of improving rate and cycle performance without increasing the proportion of conductive agent, and can effectively reduce the resistivity of the plate, ensuring that the proportion of conductive agent does not increase, the proportion of main material does not decrease, and the battery energy density is improved.
[0014] As a preferred technical solution of the present invention, the tortuosity of the first active coating is greater than the tortuosity of the second active coating.
[0015] Preferably, the porosity of the first active coating is smaller than the porosity of the second active coating.
[0016] In the present invention, if the second active coating has a large tortuosity and a small porosity, the migration of lithium ions in the second active coating will be hindered, the ion migration rate will be reduced, and the concentration polarization will increase, thereby reducing the rate and cycle performance of the battery.
[0017] Preferably, the thickness ratio of the first active coating layer to the second active coating layer is (45-53):(53-57), for example, it can be 45:53, 47:53, 49:53, 53:53, 45:57, 53:55 or 53:57, etc.
[0018] In the present invention, if the thickness ratio of the first active coating and the second active coating is too small, the electrode will swell too much after absorbing liquid, making the internal resistance of the battery too high, affecting the rate performance of the battery; if the thickness ratio of the first active coating and the second active coating is too large, the overall porosity of the electrode will be low, thereby reducing the diffusion rate of lithium ions and affecting the rate and cycle performance of the battery.
[0019] Preferably, the double-sided surface density of the positive electrode sheet is 450-600 g / m 2 , for example, it can be 450g / m 2 , 500g / m 2 , 550g / m 2 or 600g / m 2 wait.
[0020] Preferably, the ratio of the surface density of the first active coating layer to the second active coating layer is (0.8-1):1, for example, it can be 0.8:1, 0.85:1, 0.9:1, 0.95:1 or 1:1, etc.
[0021] As a preferred technical solution of the present invention, the positive electrode current collector includes aluminum foil.
[0022] As a preferred technical solution of the present invention, the film liquid absorption rate of the low swelling binder in the electrolyte is 5-10%, for example, it can be 5%, 6%, 7%, 8%, 9% or 10%.
[0023] Preferably, the liquid absorption rate of the high swelling binder in the electrolyte is 70-80%, for example, 70%, 80%, 90% or 100%.
[0024] In the present invention, by utilizing the high swelling property of the high swelling binder, the tortuosity of the top layer of the electrode sheet after injection can be significantly smaller than that of the lower layer, and the porosity of the top layer can be larger than that of the lower layer, thereby changing the tortuosity and porosity distribution of the electrode sheet, improving the migration and diffusion rate of lithium ions on the surface, reducing concentration polarization, and improving the rate and cycle performance of the battery. If the film liquid absorption rate of the high swelling binder in the electrolyte is too low, that is, less than 70%, an effective porosity gradient distribution cannot be formed, and the migration and diffusion rate of lithium ions on the surface cannot be effectively improved.
[0025] Preferably, the low swelling binder comprises modified polyacrylate.
[0026] Preferably, the modified polyacrylate includes any one of polymethyl acrylate, polyethyl acrylate, 2-methylpolymethyl acrylate or 2-methylpolyethyl acrylate, or a combination of at least two thereof.
[0027] Preferably, the high swelling binder comprises hydrogenated nitrile rubber.
[0028] As a preferred technical solution of the present invention, the particle size D50 of the first main material is 0.8-2 μm, for example, it can be 0.8 μm, 1 μm, 1.5 μm or 2 μm.
[0029] Preferably, the particle size D50 of the second main material is 6-9 μm, for example, 6 μm, 7 μm, 8 μm or 9 μm.
[0030] In the present invention, the particle size D50 of the second main material is set to be larger than the particle size D50 of the first main material because the porosity of the main material with a larger particle size is greater than that of the main material with a smaller particle size after compaction, which is more conducive to forming a pore gradient distribution and improving the migration and diffusion rate of lithium ions on the surface.
[0031] Preferably, the first main material and the second main material independently include any one of lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide or lithium nickel cobalt manganese oxide, or a combination of at least two thereof.
[0032] It should be noted that the present invention does not limit the preparation method of the first main material or the second main material. Exemplary methods include high temperature solid phase reaction method, carbon thermal reduction method, hydrothermal method, sol-gel method or co-precipitation method.
[0033] Preferably, the first conductive agent and the second conductive agent independently include any one of granular carbon material, carbon nanotubes, conductive carbon fibers or graphene, or a combination of at least two thereof.
[0034] It should be noted that the present invention does not limit the specific type of the granular carbon material. For example, it may be acetylene black, carbon black or Ketjen black.
[0035] In a second aspect, the present invention provides a method for preparing the positive electrode sheet as described in the first aspect, the preparation method comprising the following steps:
[0036] (1) mixing a first main material, a first conductive agent, a low swelling binder and a first solvent to obtain a first positive electrode slurry, and mixing a second main material, a second conductive agent, a high swelling binder and a second solvent to obtain a second positive electrode slurry;
[0037] (2) A double-layer coating method is used to sequentially coat the first positive electrode slurry and the second positive electrode slurry on at least one side of the positive electrode current collector, and after annealing, a first active coating layer and a second active coating layer are formed to obtain the positive electrode sheet.
[0038] As a preferred technical solution of the present invention, in the first positive electrode slurry of step (1), the relationship between the first conductive agent, the low swelling binder, the tortuosity of the first active coating and the porosity of the first active coating is as shown in Formula 1:
[0039] 19.5≤(a1+b1)×100×100 / (t1 / k1)≤30 Formula 1
[0040] Wherein, a1 is the mass content of the low swelling binder in the first positive electrode slurry, b1 is the mass content of the first conductive agent in the first positive electrode slurry, t1 is the tortuosity of the first active coating, and k1 is the porosity of the first active coating. For example, it can be 19.5, 20, 22, 24, 26, 28 or 30, etc.
[0041] In the present invention, the relationship among the first conductive agent, the low swelling binder, the tortuosity of the first active coating and the porosity of the first active coating satisfies Formula 1, which helps to form an effective porosity gradient.
[0042] Preferably, in step (1), the solid content of the first positive electrode slurry is 53-65wt%, for example, 53wt%, 55wt%, 60wt% or 65wt%.
[0043] Preferably, in step (1), the mass ratio of the first main material, the first conductive agent and the low swelling binder is (96.5-98.2):(0.6-1.5):(1.2-2), wherein the selection range of the first main material is "96.5-98.2", for example, it can be 96.5, 97, 97.5 or 98, etc., the selection range of the first conductive agent is "0.6-1.5", for example, it can be 0.6, 0.8, 1, 1.2 or 1.5, etc., and the selection range of the low swelling binder is "1.2-2", for example, it can be 1.2, 1.4, 1.6, 1.8 or 2, etc.
[0044] As a preferred technical solution of the present invention, in the second positive electrode slurry of step (1), the relationship between the second conductive agent, the high swelling binder, the tortuosity of the second active coating and the porosity of the second active coating is as shown in Formula 2:
[0045] 61.1≤(a2+b2)×100×100 / (t2 / k2)≤72.6 Formula 2 Wherein, a2 is the mass content of the high swelling binder in the second positive electrode slurry, b2 is the mass content of the second conductive agent in the second positive electrode slurry, t2 is the tortuosity of the second active coating, and k2 is the porosity of the second active coating. Exemplary, for example, may be 61.1, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71 or 72.6, etc.
[0046] In the present invention, the relationship between the second conductive agent, the high swelling binder, the tortuosity of the second active coating and the porosity of the second active coating satisfies Formula 2, which helps to form an effective porosity gradient.
[0047] Preferably, in step (1), the solid content of the second positive electrode slurry is 53-65wt%, for example, 53wt%, 55wt%, 60wt% or 65wt%.
[0048] Preferably, in step (1), the mass ratio of the second main material, the second conductive agent and the high swelling binder is (96.8-98.3):(0.5-1.4):(1.2-1.8), wherein the selection range of the second main material is "96.8-98.3", for example, it can be 96.8, 97, 97.5 or 98, etc., the selection range of the second conductive agent is "0.5-1.4", for example, it can be 0.5, 0.8, 1, 1.2 or 1.4, etc., and the selection range of the high swelling binder is "1.2-1.8", for example, it can be 1.2, 1.4, 1.6 or 1.8, etc.
[0049] As a preferred technical solution of the present invention, in step (1), the mass ratio of the first main material to the second main material is (0.99-1.02):1, for example, it can be 0.99:1, 1:1, 1.01:1 or 1.02:1, etc.
[0050] Preferably, in step (1), the mass ratio of the first conductive agent to the second conductive agent is (1.07-1.4):1, for example, it can be 1.07:1, 1.1:1, 1.2:1, 1.3:1 or 1.4:1.
[0051] In the present invention, the mass ratio of the first conductive agent to the second conductive agent is (1.07-1.4):1, which can change the tortuosity and porosity of the positive electrode plate, so that the tortuosity of the second active coating is smaller than that of the first active coating, and the porosity of the second active coating is larger than that of the first active coating, which is beneficial to improving the migration rate of surface lithium ions and reducing concentration polarization, thereby improving the battery rate and cycle performance.
[0052] Preferably, the mass ratio of the low swelling binder to the high swelling binder in step (1) is (0.99-1.25):1, for example, it can be 0.99:1, 1:1, 1.1:1, 1.15:1, 1.2:1 or 1.25:1, etc.
[0053] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0054] (1) stirring and dissolving a low swelling binder in N-methylpyrrolidone, and then sequentially adding a first conductive agent, a first main material and N-methylpyrrolidone under stirring to obtain a first positive electrode slurry;
[0055] The high swelling binder is stirred and dissolved in N-methylpyrrolidone, and then the second conductive agent, the second main material and N-methylpyrrolidone are sequentially added under stirring to obtain a second positive electrode slurry;
[0056] (2) The first positive electrode slurry and the second positive electrode slurry are respectively transferred to two different storage tanks of an extrusion coater with a dual die head, and are simultaneously coated on both sides of the positive electrode current collector by extrusion. After coating, they are baked at a temperature of 85-115°C (for example, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C or 115°C, etc.) for 2-6 min (for example, 2 min, 3 min, 4 min, 5 min or 6 min, etc.) to form a first active coating and a second active coating, thereby obtaining the positive electrode sheet.
[0057] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the first aspect.
[0058] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] The present invention introduces different types of binders and conductive agents of different proportions into the first active coating and the second active coating, thereby changing the tortuosity and porosity of the positive electrode plate, so that the tortuosity of the second active coating is smaller than that of the first active coating, and the porosity of the second active coating is larger than that of the first active coating, effectively improving the diffusion rate of lithium ions during the charge and discharge process, reducing the concentration polarization of the surface layer of the plate, and significantly improving the rate and cycle performance of the battery. In particular, the positive electrode plate can achieve the goal of improving the rate and cycle performance without increasing the proportion of the conductive agent, and can effectively reduce the resistivity of the plate and improve the energy density of the battery. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0062] Example 1
[0063] This embodiment provides a positive electrode plate, the positive electrode plate comprising:
[0064] A positive electrode current collector, wherein the positive electrode current collector is aluminum foil;
[0065] A first active coating disposed on both sides of the positive electrode current collector, wherein the raw materials of the first active coating include a first main material, a first conductive agent and a low swelling binder, wherein the first main material is lithium iron phosphate with a particle size D50 of 1.5 μm, the first conductive agent includes conductive carbon black and carbon nanotubes, and the low swelling binder is a modified polyacrylate with a film liquid absorption rate of 8%;
[0066] A second active coating is disposed on the surface of the first active coating on the side relatively far from the positive electrode current collector, wherein the raw materials of the second active coating include a second main material, a second conductive agent and a high swelling binder, wherein the second main material is lithium iron phosphate with a particle size D50 of 8 μm, the second conductive agent includes conductive carbon black and carbon nanotubes, and the high swelling binder is hydrogenated nitrile rubber with a film liquid absorption rate of 75%;
[0067] The tortuosity of the first active coating is greater than the tortuosity of the second active coating, and the porosity of the first active coating is less than the porosity of the second active coating;
[0068] The thickness ratio of the first active coating layer to the second active coating layer is 50:55;
[0069] The double-sided surface density of the positive electrode sheet is 500g / m 2 The ratio of the surface density of the first active coating layer to that of the second active coating layer is 0.9:1.
[0070] This embodiment also provides a method for preparing the above-mentioned positive electrode sheet, and the preparation method comprises the following steps:
[0071] (1) 0.065 kg of polyacrylate was dissolved in 0.996 kg of N-methylpyrrolidone by stirring, and then 0.035 kg of conductive carbon black and 0.025 kg of carbon nanotubes were added in sequence under stirring, and stirred for 1 hour, and then 4.875 kg of lithium iron phosphate and 2.334 kg of N-methylpyrrolidone were added in sequence, and stirred for 2 hours to obtain a first positive electrode slurry with a solid content of 60 wt%;
[0072] 0.065 kg of hydrogenated nitrile rubber was stirred and dissolved in 0.864 kg of N-methylpyrrolidone, and then 0.025 kg of conductive carbon black and 0.020 kg of carbon nanotubes were added in sequence under stirring, and stirred for 1 hour, and then 4.89 kg of lithium iron phosphate and 2.469 kg of N-methylpyrrolidone were added in sequence, and stirred for 2 hours to obtain a second positive electrode slurry with a solid content of 60 wt%;
[0073] (2) The first positive electrode slurry and the second positive electrode slurry are respectively transferred to two different storage tanks of an extrusion coater with a double die head, and are simultaneously coated on both sides of the positive electrode current collector by extrusion, with a total coating thickness of 290 μm. After coating, the coating is baked at a temperature of 100° C. for 4 min to form a first active coating and a second active coating, thereby obtaining the positive electrode sheet;
[0074] The relationship among the first conductive agent, the low swelling binder, the tortuosity of the first active coating and the porosity of the first active coating is as shown in Formula 1:
[0075] (a1+b1)×100×100 / (t1 / k1)=27.78 Formula 1;
[0076] The relationship between the second conductive agent, the high swelling binder, the tortuosity of the second active coating and the porosity of the second active coating is shown in Formula 2:
[0077] (a2+b2)×100×100 / (t2 / k2)=67.69 Formula 2.
[0078] Example 2
[0079] This embodiment provides a positive electrode plate, the positive electrode plate comprising:
[0080] A positive electrode current collector, wherein the positive electrode current collector is aluminum foil;
[0081] A first active coating disposed on both sides of the positive electrode current collector, wherein the raw materials of the first active coating include a first main material, a first conductive agent and a low swelling binder, wherein the first main material is lithium iron phosphate with a particle size D50 of 0.8 μm, the first conductive agent includes conductive carbon black and carbon nanotubes, and the low swelling binder is a polyacrylate with a film liquid absorption rate of 8%;
[0082] A second active coating is disposed on the surface of the first active coating on the side relatively far from the positive electrode current collector, wherein the raw materials of the second active coating include a second main material, a second conductive agent and a high swelling binder, wherein the second main material is lithium iron phosphate with a particle size D50 of 6 μm, the second conductive agent includes conductive carbon black and carbon nanotubes, and the high swelling binder is hydrogenated nitrile rubber with a film liquid absorption rate of 75%;
[0083] The tortuosity of the first active coating is greater than the tortuosity of the second active coating, and the porosity of the first active coating is less than the porosity of the second active coating;
[0084] The thickness ratio of the first active coating layer to the second active coating layer is 45:57;
[0085] The double-sided surface density of the positive electrode sheet is 450g / m2 The ratio of the surface density of the first active coating layer to that of the second active coating layer is 0.8:1.
[0086] This embodiment also provides a method for preparing the above-mentioned positive electrode sheet, and the preparation method comprises the following steps:
[0087] (1) 0.065 kg of polyacrylate was dissolved in 0.996 kg of N-methylpyrrolidone by stirring, and then 0.035 kg of conductive carbon black and 0.025 kg of carbon nanotubes were added in sequence under stirring, and stirred for 1 hour, and then 4.875 kg of lithium iron phosphate and 3.429 kg of N-methylpyrrolidone were added in sequence, and stirred for 2 hours to obtain a first positive electrode slurry with a solid content of 53 wt%;
[0088] 0.065 kg of hydrogenated nitrile rubber was stirred and dissolved in 0.864 kg of N-methylpyrrolidone, and then 0.025 kg of conductive carbon black and 0.020 kg of carbon nanotubes were added in sequence under stirring, and stirred for 1 hour, and then 4.89 kg of lithium iron phosphate and 3.570 kg of N-methylpyrrolidone were added in sequence, and stirred for 2 hours to obtain a second positive electrode slurry with a solid content of 53 wt%;
[0089] (2) The first positive electrode slurry and the second positive electrode slurry are respectively transferred to two different storage tanks of an extrusion coater with a double die head, and are simultaneously coated on both sides of the positive electrode current collector by extrusion. The total coating thickness is 260 μm. After the coating is completed, the coating is baked at a temperature of 85° C. for 6 minutes to form a first active coating and a second active coating, thereby obtaining the positive electrode sheet;
[0090] The relationship among the first conductive agent, the low swelling binder, the tortuosity of the first active coating and the porosity of the first active coating is as shown in Formula 1:
[0091] (a1+b1)×100×100 / (t1 / k1)=25.00 Formula 1;
[0092] The relationship between the second conductive agent, the high swelling binder, the tortuosity of the second active coating and the porosity of the second active coating is shown in Formula 2:
[0093] (a2+b2)×100×100 / (t2 / k2)=63.07 Formula 2.
[0094] Example 3
[0095] This embodiment provides a positive electrode plate, the positive electrode plate comprising:
[0096] A positive electrode current collector, wherein the positive electrode current collector is aluminum foil;
[0097] A first active coating disposed on both sides of the positive electrode current collector, wherein the raw materials of the first active coating include a first main material, a first conductive agent and a low swelling binder, wherein the first main material is lithium iron phosphate with a particle size D50 of 2 μm, the first conductive agent includes conductive carbon black and carbon nanotubes, and the low swelling binder is a polyacrylate with a film liquid absorption rate of 8%;
[0098] A second active coating is disposed on the surface of the first active coating on the side relatively far from the positive electrode current collector, wherein the raw materials of the second active coating include a second main material, a second conductive agent and a high swelling binder, wherein the second main material is lithium iron phosphate with a particle size D50 of 9 μm, the second conductive agent includes conductive carbon black and carbon nanotubes, and the high swelling binder is hydrogenated nitrile rubber with a film liquid absorption rate of 75%;
[0099] The tortuosity of the first active coating is greater than the tortuosity of the second active coating, and the porosity of the first active coating is less than the porosity of the second active coating;
[0100] The thickness ratio of the first active coating layer to the second active coating layer is 53:53;
[0101] The double-sided surface density of the positive electrode sheet is 600g / m 2 , the ratio of the surface density of the first active coating and the second active coating is 1:1.
[0102] This embodiment also provides a method for preparing the above-mentioned positive electrode sheet, and the preparation method comprises the following steps:
[0103] (1) 0.065 kg of polyacrylate was dissolved in 0.996 kg of N-methylpyrrolidone by stirring, and then 0.035 kg of conductive carbon black and 0.025 kg of carbon nanotubes were added in sequence under stirring, and stirred for 1 hour, and then 4.875 kg of lithium iron phosphate and 1.696 kg of N-methylpyrrolidone were added in sequence, and stirred for 2 hours to obtain a first positive electrode slurry with a solid content of 65 wt%;
[0104] 0.065 kg of hydrogenated nitrile rubber was stirred and dissolved in 0.864 kg of N-methylpyrrolidone, and then 0.025 kg of conductive carbon black and 0.020 kg of carbon nanotubes were added in sequence under stirring, and stirred for 1 hour, and then 4.89 kg of lithium iron phosphate and 1.828 kg of N-methylpyrrolidone were added in sequence, and stirred for 2 hours to obtain a second positive electrode slurry with a solid content of 65 wt%;
[0105] (2) The first positive electrode slurry and the second positive electrode slurry are respectively transferred to two different storage tanks of an extrusion coater with a double die head, and are simultaneously coated on both sides of the positive electrode current collector by extrusion, with a total coating thickness of 350 μm. After coating, the coating is baked at a temperature of 115° C. for 2 min to form a first active coating and a second active coating, thereby obtaining the positive electrode sheet;
[0106] The relationship among the first conductive agent, the low swelling binder, the tortuosity of the first active coating and the porosity of the first active coating is as shown in Formula 1:
[0107] (a1+b1)×100×100 / (t1 / k1)=29.25 Formula 1;
[0108] The relationship between the second conductive agent, the high swelling binder, the tortuosity of the second active coating and the porosity of the second active coating is shown in Formula 2:
[0109] (a2+b2)×100×100 / (t2 / k2)=70.71 Formula 2.
[0110] Example 4
[0111] The difference between this embodiment and embodiment 1 is that the porosity of the first active coating is equal to the porosity of the second active coating by adjusting the ratio of the first conductive agent, the second conductive agent, the low swelling binder and the low swelling binder.
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Example 5
[0114] The difference between this embodiment and embodiment 1 is that the porosity of the first active coating is greater than the porosity of the second active coating by adjusting the ratio of the first conductive agent, the second conductive agent, the low swelling binder and the low swelling binder.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Example 6
[0117] The difference between this embodiment and embodiment 1 is that the tortuosity of the first active coating is equal to the tortuosity of the second active coating by adjusting the ratio of the first conductive agent, the second conductive agent, the low swelling binder and the low swelling binder.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Example 7
[0120] The difference between this embodiment and embodiment 1 is that the tortuosity of the first active coating is smaller than the tortuosity of the second active coating by adjusting the ratio of the first conductive agent, the second conductive agent, the low swelling binder and the low swelling binder.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Example 8
[0123] The difference between this embodiment and embodiment 1 is that the thickness ratio of the first active coating layer to the second active coating layer is 40:57.
[0124] The rest of the preparation methods and parameters were the same as those in Example 1.
[0125] Example 9
[0126] The difference between this embodiment and embodiment 1 is that the thickness ratio of the first active coating layer to the second active coating layer is 53:50.
[0127] The rest of the preparation methods and parameters were the same as those in Example 1.
[0128] Example 10
[0129] The difference between this embodiment and embodiment 1 is that the relationship among the first conductive agent, the low swelling binder, the tortuosity of the first active coating layer and the porosity of the first active coating layer does not satisfy equation 1.
[0130] The rest of the preparation methods and parameters were the same as those in Example 1.
[0131] Embodiment 11
[0132] The difference between this embodiment and embodiment 1 is that the relationship among the second conductive agent, the high swelling binder, the tortuosity of the second active coating and the porosity of the second active coating does not satisfy Formula 2.
[0133] The rest of the preparation methods and parameters were the same as those in Example 1.
[0134] Comparative Example 1
[0135] This comparative example provides a method for preparing a positive electrode sheet, and the preparation method comprises the following steps:
[0136] (1) Weigh 0.065 kg of PVDF binder, stir and dissolve it in 0.996 kg of N-methylpyrrolidone to prepare a PVDF glue solution;
[0137] 0.035 kg of conductive carbon black and 0.025 kg of carbon nanotubes were added to the PVDF glue solution in sequence under stirring, and stirred for 1 hour to fully disperse the conductive agent. Then 4.875 kg of lithium iron phosphate and 2.334 kg of N-methylpyrrolidone were added step by step and stirred for 2 hours to prepare a positive electrode slurry.
[0138] (2) The positive electrode slurry was transferred to a storage tank of an extrusion coater with a single die head, and was coated on both sides of the aluminum foil by extrusion. The total coating thickness was 290 μm, and the double-sided surface density of the coating was 500 g / m 2 The positive electrode sheet can be obtained by baking at 100° C. for 3 minutes.
[0139] Comparative Example 2
[0140] The difference between this comparative example and Example 1 is that the low swelling binder is replaced by a high swelling binder hydrogenated nitrile rubber.
[0141] The rest of the preparation methods and parameters were the same as those in Example 1.
[0142] Comparative Example 3
[0143] The difference between this comparative example and Example 1 is that the high swelling binder is replaced by a low swelling binder polyacrylate.
[0144] The rest of the preparation methods and parameters were the same as those in Example 1.
[0145] Performance Testing
[0146] (I) The porosity and tortuosity of the first active coating and the second active coating of the positive electrode sheets provided in the above-mentioned embodiments and comparative examples were tested by cross-sectional CT scanning method, and the test results are shown in Tables 1 and 2.
[0147] Table 1
[0148]
[0149]
[0150] Table 2
[0151]
[0152] analyze:
[0153] It can be seen from Table 1 and Table 2 that the preparation method proposed in the present invention, that is, using a high swelling binder for the second active coating and a low swelling binder for the first active coating, can reduce the tortuosity of the second active coating and increase the porosity of the second active coating, so that the tortuosity of the second active coating is 0.8-2.3 smaller than that of the first active coating, and the porosity of the second active coating is 6-20% higher than that of the first active coating.
[0154] (ii) The positive electrode plates provided in the above-mentioned embodiments and comparative examples were respectively tested for their resistivity by a four-probe resistance tester. The test results are shown in Table 3.
[0155] Table 3
[0156]
[0157]
[0158] analyze:
[0159] It can be seen from Table 3 that the positive electrode sheet prepared by the preparation method provided by the present invention can obtain a lower sheet resistivity.
[0160] (III) The positive electrode sheets provided in the above embodiments and comparative examples are used to prepare lithium-ion batteries, and the preparation method is as follows:
[0161] (I) rolling the positive electrode sheet to form a rolled positive electrode sheet with a compaction density of 2.55 g / cc, and cutting the rolled positive electrode sheet into a desired size;
[0162] (II) Graphite, conductive agent SP, thickener CMC and binder SBR are mixed uniformly in a mass ratio of 96.5:1.0:1.0:1.5 to obtain a negative electrode material, and then the negative electrode material is added to a solvent deionized water, and fully stirred to obtain a mixed slurry, and then the mixed slurry is uniformly coated on a copper foil, and after drying, rolling and cutting, a negative electrode sheet is obtained;
[0163] (3) Electrolyte: A conventional lithium iron phosphate electrolyte on the market was selected, wherein the concentration of LiPF6 was 1.1 mol / L, and the mass ratio of the mixed solvent components was ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 2.5:4.0:3.5;
[0164] (4) Assemble the positive electrode sheet, the negative electrode sheet, the separator (made of polyethylene) and the electrolyte to obtain a lithium-ion battery.
[0165] The above lithium-ion battery is subjected to performance testing, and the testing method is as follows:
[0166] 1) Rate discharge test: At 25°C, charge to 3.65V at 0.5C constant current, charge to 0.05C at constant voltage, let stand for 30 minutes, then discharge to 2.0V at 0.1C, 0.33C, 0.5C, 1C, and 2C constant currents, and compare the discharge capacity ratios at different rates.
[0167] 2) Cycle test: At 25°C and 45°C, charge to 3.65V at 1C constant current, charge to 0.05C at constant voltage, let stand for 30 minutes, then discharge to 2.0V at 1C constant current, cycle 1000 times, and compare capacity retention rate.
[0168] The above test results are shown in Table 4 and Table 5.
[0169] Table 4
[0170]
[0171]
[0172] Table 5
[0173]
[0174]
[0175] analyze:
[0176] It can be seen from Tables 4 and 5 that the present invention changes the pole piece tortuosity and pore distribution by means of binders of different swelling types, so that the tortuosity of the first active coating is greater than that of the second active coating, and the porosity of the first active coating is less than that of the second active coating, thereby improving the surface lithium ion migration and diffusion rate, reducing concentration polarization, and significantly improving the rate and cycle performance of high surface density electrode batteries. The 2C rate discharge ratio is increased by about 5%, the capacity retention rate of 1000 cycles at 25°C is increased by about 7%, and the capacity retention rate of 1000 cycles at 45°C is increased by about 5-6%.
[0177] It can be seen from Examples 1 and 4-7 that if the second active coating has a large tortuosity and a small porosity, the migration of lithium ions in the second active coating will be hindered and the ion migration rate will be reduced, resulting in increased concentration polarization, thereby reducing the battery rate and cycle performance.
[0178] It can be seen from Example 1 and Examples 8-9 that if the thickness ratio of the first active coating and the second active coating is too small, the overall swelling of the electrode will be too large, which will increase the resistivity of the electrode and deteriorate the rate and cycle performance of the battery; if the thickness ratio of the first active coating and the second active coating is too large, the overall porosity of the electrode will be too small and the tortuosity will be too large, which will increase the resistivity of the electrode and deteriorate the rate and cycle performance of the battery.
[0179] It can be seen from Examples 1 and 10-11 that if the relationship between the first conductive agent, the low swelling binder, the tortuosity of the first active coating and the porosity of the first active coating does not satisfy Formula 1, or the relationship between the second conductive agent, the high swelling binder, the tortuosity of the second active coating and the porosity of the second active coating does not satisfy Formula 2, the resistivity of the electrode increases and the rate and cycle performance of the battery deteriorate.
[0180] It can be seen from Example 1 and Comparative Examples 1-3 that if the same type of binder is used, the first and second active layers fail to form an effective gradient of porosity and tortuosity distribution, and cannot effectively reduce the electrode resistivity and improve the battery rate and cycle performance.
[0181] The applicant declares that the present invention illustrates the technical solution of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises: Positive electrode current collector; A first active coating disposed on at least one side of the positive electrode current collector, wherein the raw materials of the first active coating include a first main material, a first conductive agent and a low swelling binder; A second active coating is disposed on a surface of the first active coating on a side relatively away from the positive electrode current collector, wherein raw materials of the second active coating include a second main material, a second conductive agent and a high swelling binder.
2. The positive electrode sheet according to claim 1, characterized in that: The tortuosity of the first active coating is greater than the tortuosity of the second active coating; Preferably, the porosity of the first active coating is less than the porosity of the second active coating; Preferably, the thickness ratio of the first active coating layer to the second active coating layer is (45-53):(53-57); Preferably, the double-sided surface density of the positive electrode sheet is 450-600 g / m 2 ; Preferably, the ratio of the surface density of the first active coating to that of the second active coating is (0.8-1):
1.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The film liquid absorption rate of the low swelling binder in the electrolyte is 5-10%; Preferably, the film liquid absorption rate of the high swelling binder in the electrolyte is 70-80%; Preferably, the low swelling binder comprises modified polyacrylate; Preferably, the modified polyacrylate comprises any one or a combination of at least two of polymethyl acrylate, polyethyl acrylate, 2-methylpolymethyl acrylate or 2-methylpolyethyl acrylate; Preferably, the high swelling binder comprises hydrogenated nitrile rubber.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The particle size D50 of the first main material is 0.8-2 μm; Preferably, the particle size D50 of the second main material is 6-9 μm; Preferably, the first main material and the second main material independently include any one of lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide or lithium nickel cobalt manganese oxide, or a combination of at least two thereof; Preferably, the first conductive agent and the second conductive agent independently include any one of granular carbon material, carbon nanotubes, conductive carbon fibers or graphene, or a combination of at least two thereof.
5. A method for preparing a positive electrode sheet according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing a first main material, a first conductive agent, a low swelling binder and a first solvent to obtain a first positive electrode slurry, and mixing a second main material, a second conductive agent, a high swelling binder and a second solvent to obtain a second positive electrode slurry; (2) A double-layer coating method is used to sequentially coat the first positive electrode slurry and the second positive electrode slurry on at least one side of the positive electrode current collector, and after baking, a first active coating layer and a second active coating layer are formed to obtain the positive electrode sheet.
6. The preparation method according to claim 5, characterized in that: Step (1) In the first positive electrode slurry, the relationship between the first conductive agent, the low swelling binder, the tortuosity of the first active coating and the porosity of the first active coating is as shown in Formula 1: 19.5≤(a1+b1)×100×100 / (t1 / k1)≤30 Formula 1 wherein a1 is the mass content of the low swelling binder in the first positive electrode slurry, b1 is the mass content of the first conductive agent in the first positive electrode slurry, t1 is the tortuosity of the first active coating, and k1 is the porosity of the first active coating; Preferably, the solid content of the first positive electrode slurry in step (1) is 53-65wt%; Preferably, in step (1), the mass ratio of the first main material, the first conductive agent and the low swelling binder is (96.5-98.2):(0.6-1.5):(1.2-2).
7. The preparation method according to claim 5 or 6, characterized in that: Step (1) In the second positive electrode slurry, the relationship between the second conductive agent, the high swelling binder, the tortuosity of the second active coating and the porosity of the second active coating is as shown in Formula 2: 61.1≤(a2+b2)×100×100 / (t2 / k2)≤72.6 Formula 2 wherein a2 is the mass content of the high swelling binder in the second positive electrode slurry, b2 is the mass content of the second conductive agent in the second positive electrode slurry, t2 is the tortuosity of the second active coating, and k2 is the porosity of the second active coating; Preferably, the solid content of the second positive electrode slurry in step (1) is 53-65wt%; Preferably, in step (1), the mass ratio of the second main material, the second conductive agent and the high swelling binder is (96.8-98.3):(0.5-1.4):(1.2-1.8).
8. The preparation method according to any one of claims 5 to 7, characterized in that: Step (1) The mass ratio of the first main material to the second main material is (0.99-1.02):1; Preferably, in step (1), the mass ratio of the first conductive agent to the second conductive agent is (1.07-1.4):1; Preferably, the mass ratio of the low swelling binder to the high swelling binder in step (1) is (0.99-1.25):
1.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The preparation method comprises the following steps: (1) stirring and dissolving a low swelling binder in N-methylpyrrolidone, and then sequentially adding a first conductive agent, a first main material and N-methylpyrrolidone under stirring to obtain a first positive electrode slurry; The high swelling binder is stirred and dissolved in N-methylpyrrolidone, and then the second conductive agent, the second main material and N-methylpyrrolidone are sequentially added under stirring to obtain a second positive electrode slurry; (2) The first positive electrode slurry and the second positive electrode slurry are respectively transferred to two different storage tanks of an extrusion coater with a dual die head, and are simultaneously coated on both sides of the positive electrode current collector by extrusion. After coating, they are baked at a temperature of 85-115° C. for 2-6 minutes to form a first active coating and a second active coating, thereby obtaining the positive electrode sheet.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as described in any one of claims 1 to 4.
Citation Information
Patent Citations
Lithium iron phosphate thick electrode and preparation method and application thereof
CN115394961A
Lithium-sulfur battery positive plate, preparation method thereof and lithium-sulfur battery
CN115692602A
Preparation method of electrode plate
CN116682942A
Cited By
Positive pole piece, battery and electric equipment
CN119447183A
Positive electrode sheet, battery, and electric device
CN119447183B
Electrode plate, preparation method thereof and battery
CN120413604A